Efficient hydrogen storage with the combination of metal Mg and porous nanostructured material. (21st June 2019) - Liang, Hui; Chen, Dandan; Thiry, Damien; Li, Wenjiang; Chen, Minfang; Snyders, Rony
Abstract: High-energy density and low cost magnesium nanoparticles (Mg NPs)-based material are being sought to meet increasing capable of hydrogen (H2 ) storage demand. Here, a kind of air-stable Mg NPs supported on porous structured multi-walled carbon tubes-polymethyl methacrylate (MWCNTs-PMMA) template is prepared owing to reversible well-distributed, dispersed and small-sized Mg/MgH2 NPs. The aim is to improve the H2 storage capacity, hydrogen sorption kinetics and thermodynamics of nano Mg-based system without using catalyst. The organic Mg precursor was directly in-situ reduced to metallic Mg NPs in MWCNTs-PMMA template by lithium naphthalide. The size distribution of reduced Mg nanoparticles is around 3.6 ± 0.2 nm, confirmed by XRD and TEM analyses, which is due to the strong interaction between Mg NPs and MWCNTs-PMMA via PMMA binding Mg 2+, as well as the confinement of porous template hindered the growth and agglomeration of Mg NPs. Moreover, except H2, O2 and H2 O molecules can't infiltrate the porous structure of MWCNTs-PMMA resulted in the presence of air stable Mg NPs in the MWCNTs-PMMA. The work provides a new scope to prepare nano metal-based composite for H2 storage. Highlights: Organic Mg precursor was in-situ reduced to well-dispersed metallic Mg NPs on porous MWCNTs-PMMA template. Mg NPs were supported on MWCNTs-PMMA templates avoiding nanotube debundling. The microstructure and H2 sorption performance of MWCNTs-PMMA-Mg NPs composites are stable to air exposure. MWCNTs-PMMA-Mg NPs composite can uptake/release H2 below 200 °C within 30 min. MWCNTs-PMMA-Mg NPs composite exhibited hydrogen absorption capacity of 6.7 wt% and rapid H2 sorption kinetic.